2024
DOI: 10.3389/fmed.2024.1312929
|View full text |Cite
|
Sign up to set email alerts
|

Skin and hard surface disinfection against Candida auris – What we know today

Soraya Omardien,
Peter Teska

Abstract: Candida auris has emerged as a global healthcare threat, displaying resistance to important healthcare antifungal therapies. Infection prevention and control protocols have become paramount in reducing transmission of C. auris in healthcare, of which cleaning and disinfection plays an important role. Candida albicans is used as a surrogate yeast for yeasticidal claims of disinfection products, but reports have been made that sensitivity to disinfectants by C. auris differs from its surrogate. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…A wide variety of products and experimental methods have been tested to disinfect environmental surfaces contaminated with C. auris [107]. However, the findings of these studies have not always been consistent [108]. Several studies have demonstrated the effectiveness of Chlor-Clean and Haz-Tab, which are chlorine-based products with concentrations of 1000 ppm and 10,000 ppm, respectively, in eradicating clinical isolates of C. auris within 3 min of contact [109].…”
Section: Strategies For Preventing the Transmission And Colonisation ...mentioning
confidence: 99%
“…A wide variety of products and experimental methods have been tested to disinfect environmental surfaces contaminated with C. auris [107]. However, the findings of these studies have not always been consistent [108]. Several studies have demonstrated the effectiveness of Chlor-Clean and Haz-Tab, which are chlorine-based products with concentrations of 1000 ppm and 10,000 ppm, respectively, in eradicating clinical isolates of C. auris within 3 min of contact [109].…”
Section: Strategies For Preventing the Transmission And Colonisation ...mentioning
confidence: 99%
“…UVC LEDs may be a feasible and scalable method for environmental disinfection with technical applications in water, air, surface, and waste disinfection [48][49][50][51][52][53][54][55][56][57]. This review provides a comprehensive analysis and critical discussion of the relevant literature on the global public health threat and economic disruption relative to the rapid spread of C. auris, the feasibility of applying UVC LED disinfection technology to environmental services and waste management strategies in healthcare facilities, and the challenges to implementing robust infection prevention protocols and surveillance systems.…”
Section: Enhanced Infection Prevention and Controlmentioning
confidence: 99%
“…UVC disinfection is also specifically effective at inactivating C. auris on hard surfaces, which is common in healthcare settings [49,[51][52][53][55][56][57]215]. The use of UVC technology as an adjuvant disinfection modality for C. auris may be an advantageous environmental mitigation strategy [26].…”
Section: Surfacementioning
confidence: 99%
See 1 more Smart Citation